Identification of Fusarium Head Blight Resistance in Triticum timopheevii Accessions and Characterization of Wheat-T. timopheevii Introgression Lines for Enhanced Resistance - Steed, Andrew; King, Julie; Grewal, Surbhi; Yang, Cai-yun; Clarke, Martha; Devi, Urmila; King, Ian P.; Nicholson, Paul (Frontiers in Plant Science, 2022)
A diverse panel of wheat wild relative species was screened for resistance to Fusarium head blight (FHB) by spray inoculation. The great majority of species and accessions were susceptible or highly susceptible to FHB. Accessions of Triticum timopheevii (P95-99.1-1), Agropyron desertorum (9439957) and Elymus vaillantianus (531552) were highly resistant to FHB while additional accessions of T. timopheevii were found to be susceptible to FHB. A combination of spray and point inoculation assessments over two consecutive seasons indicated that the resistance in accession P95-99.1-1 was due to enhanced resistance to initial infection of the fungus (type 1 resistance), and not to reduction in spread (type 2 resistance). A panel of wheat-T. timopheevii (accession P95-99.1-1) introgression lines was screened for FHB resistance over two consecutive seasons using spray inoculation. Most introgression lines were similar in susceptibility to FHB as the wheat recipient (Paragon) but substitution of the terminal portion of chromosome 3BS of wheat with a similar-sized portion of 3G of T. timopheevii significantly enhanced FHB resistance in the wheat background.